A 3D-printed passive ultrasound phase-interference compensator for reduced wave degradation in cancellous bone – an experimental study in replica models. (28th March 2018) - Langton, Christian M; AlQahtani, Saeed M; Wille, Marie-Luise
The current 'active' solution to overcome the impediment of ultrasound wave degradation associated with transit-time variation in complex tissue structures, such as the skull, is to vary the transmission delay of ultrasound pulses from individual transducer elements. This article considers a novel 'passive' solution in which constant transit time is achieved by propagating through an additional material layer positioned between the ultrasound transducer and the test sample. To test the concept, replica models based on four cancellous bone natural tissue samples and their corresponding passive ultrasound phase-interference compensator were 3D-printed. Normalised broadband ultrasound attenuation was used as a quantitative measure of wave degradation, performed in transmission mode at a frequency of 1 MHz and yielding a reduction ranging from 57% to 74% when the ultrasound phase-interference compensator was incorporated. It is suggested that the passive compensator offers a broad utility and, hence, it may be applied to any ultrasound transducer, of any complexity (single element or array), frequency and dimension.